Acceleration of an interplanetary shock through the magnetosheath: a global hybrid simulation - Moissard, C.; Savoini, P.; Fontaine, D.; Modolo, R. (Frontiers in Astronomy and Space Sciences, 2024)
According to most observations and simulations, interplanetary shocks slow down when they propagate through the magnetosheath. In this article, we present results from a self-consistent global hybrid PIC simulation of an interplanetary shock which, by contrast, accelerates as it propagates through the magnetosheath. In this simulation, the solar wind upstream of the interplanetary shock is set up with an Alfv én Mach number M A = 4.5 and the interplanetary magnetic field (IMF) is set up to be almost parallel to the y direction in GSE coordinate system.The 'planet' is modelled as a magnetic dipole with no tilt: the dipole is in the GSE's z direction.In the ecliptic plane (Oxy), which contains the interplanetary magnetic field (IMF), the magnetic field lines are piling up against the magnetopause, and the velocity of the interplanetary shock decreases from 779 ± 48 km/s in the solar wind down to 607 ± 48 km/s in the magnetosheath. By contrast, in the noon-meridian plane (Oxz), which is perpendicular to the IMF, the velocity of the interplanetary shock in the magnetosheath can reach values up to 904 ± 48 km/s. This study suggests that interplanetary shocks can accelerate as they propagate through the magnetosheath.This finding, reported here for the first time, could have important implications for space weather, as it corresponds to the case where an interplanetary shock catches up with a low Alfv én Mach number solar transient such as an interplanetary coronal mass ejection.